Pengaruh Budaya dan Sistem Pengendalian pada Pencegah Fraud di Perusahaan Retail - Imam Hidayat; Icha Zakiyah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
Acts of fraud or extortion that occur in Indonesia are more popular with the term corruption, fraud by internal parties or theft from external parties which can harm companies that focus on this research in the retail sector. In addition, fraud prevention will minimize the possibility of fraud and optimize the possibility of fraud being detected. The data collection technique used is the questionnaire method, namely distributing a list of questions (questionnaires) that will be filled out and answered by respondents. In this study, the validity test will be carried out with the help of the SPSS 25 program. This is done by looking for the correlation of each question item with the total score of the question for the results of respondents' answers that have the interval measurement scale above showing all the indicators used to measure the variables used in this study resulting in r arithmetic from r table. The significance test was carried out by comparing the r table with the calculated r so that the questions measuring each research variable were declared valid.